2022
DOI: 10.1039/d1lc00633a
|View full text |Cite
|
Sign up to set email alerts
|

Printed microfluidic sweat sensing platform for cortisol and glucose detection

Abstract: An inexpensive microfluidic sweat sensor platform for single-use and continuous biomarker measurements integrated with a synthetic skin for characterization at various sweat rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 73 publications
2
46
0
Order By: Relevance
“…As shown in Figure S14b, the sensor responded faster when the external humidity was lower as the solution in the filer paper channels moved faster for a quick evaporation rate under lower humidity. However, the final detected potential value did not change, which is consistent with the former results. …”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure S14b, the sensor responded faster when the external humidity was lower as the solution in the filer paper channels moved faster for a quick evaporation rate under lower humidity. However, the final detected potential value did not change, which is consistent with the former results. …”
Section: Resultssupporting
confidence: 90%
“…However, current wearable sweat sensors are limited by the lack of available data revealing the effect of sweat volume flow rates [187], the mixture of old and new sweat that reduces sensor reliability [188], and above all, the requirement for expensive and complex fabrication techniques such as photolithography. Very recently, Naik et al [189] demonstrated the fabrication of a "smart bandage" microfluidic device for single-use cortisol detection and glucose sensing and monitoring. The device was composed of electrochemical sensorprinted graphene and silver inks and an adhesive-based microchannel.…”
Section: Enzymatic Biosensormentioning
confidence: 99%
“…The antibody-containing detection component of the patch can be disassembled after use, and a new component can be put in the patch for the next cortisol detection on demand. Cortisol detection electrodes can be printed on a flexible bandage as shown in Figure 5C [47]. Ag and graphene inks were printed on a polymeric substrate (polyimide) to form reference and counter electrodes, respectively.…”
Section: Wearable Sensors For Detecting Molecular Biomarkersmentioning
confidence: 99%
“…Cortisol detection electrodes can be printed on a flexible bandage as shown in Figure 5 C [ 47 ]. Ag and graphene inks were printed on a polymeric substrate (polyimide) to form reference and counter electrodes, respectively.…”
Section: Wearable Sensors For Detecting Molecular Biomarkersmentioning
confidence: 99%